New insights into iNKT cells and their roles in liver diseases - Gu, Xinyu; Chu, Qingfei; Ma, Xiao; Wang, Jing; Chen, Chao; Guan, Jun; Ren, Yanli; Wu, Shanshan; Zhu, Haihong (Frontiers in Immunology, 2022)
Natural killer T cells (NKTs) are an important part of the immune system. Since their discovery in the 1990s, researchers have gained deeper insights into the physiology and functions of these cells in many liver diseases. As part of the innate immune system, hepatic NKT cells interact with hepatocytes, macrophages (Kupffer cells), T cells, and dendritic cells through direct cell-to-cell contact and cytokine secretion, bridging the innate and adaptive immune systems. A better understanding of hepatic NKT cells is necessary for finding new methods of treating liver disease including autoimmune liver diseases, alcoholic liver diseases (ALD), non-alcoholic fatty liver diseases (NAFLD), and liver tumors. Here we summarize how NKT cells are activated, how they interact with other cells, and how they function in the presence of liver disease.